Analisis Keterampilan Berpikir Kritis Siswa Sma Negeri Pada Mata Pelajaran Geografi - Kamur, Sudarwin; Septi Andriani; Ahmad Iskandar; samsi awal; Gaby Nanda Kharisma (Mataram University, 2025)
This study aims to analyze the critical thinking skills of high school students in geography subjects in Mawasangka District. The type of research used in this study is descriptive research. The approach to this study is qualitative with a qualitative research method while the form of this research is qualitative descriptive. The instruments used were observation sheets and interview guidelines. The data analysis used is a qualitative data analysis technique according to Miles and Huberman. The subjects of this study are teachers and students of State High Schools in MawasangkaÂ district who are accredited A and B. Sampling techniques use random probability sampling. Data collection techniques with interviews, observations and documentation. Based on the results of the study, it can be seen that students' critical thinking skills from the five indicators that have been determined, namely analytical skills, synthesis skills, problem-solving skills, inference skills and evaluation skills in general, it can be concluded that students' critical thinking skills are quite good. This is evidenced by the indicators of problem-solving skills that students have are relatively less than other indicators. Meanwhile, students' skills that are classified as good are indicators of evaluating. Â